Expression analysis of genes encoding salt induced transport proteins in two contrasting rice cultivars with different salt stress tolerance - Nguyen, Duc Quan; Tran , Thi Huong Giang; Do, Huu Dung; Nguyen, Huy Hoang (Academia Journal of Biology, 2023)
Soil salinization is a serious global problem that impedes the growth and development of numerous agricultural crops worldwide. Plants have evolved a diversity of adaptive mechanisms for coping with salt stress. Among the known mechanisms, the ability of plants to maintain intracellular ions and osmotic homeostasis via exclusion and compartmentalization of salt is highly correlated with high salt stress tolerance. Several transport proteins, such as high-affinity K+ transporter 1 (HKT1), high affinity K+/Na+ transporter 10 (HAK10), salt overly sensitive 1 (SOS1), and sodium/hydrogen exchanger 1 (NHX1), have been identified to be associated with the exclusion and compartmentalization of salt. In this study, an investigation was conducted to evaluate the expression of genes encoding SOS1, HKT1, HAK10, and NHX1 transporters in the leaf and root tissues of two contrasting rice cultivars, salt tolerant DP and salt sensitive IR28, under salt stress of 150 mM NaCl by RT-qPCR approach. RT-qPCR data revealed that the expression of HKT1, HAK10, SOS1, and NXH1 were upregulated at a higher level in the DP cultivar than in the IR28 cultivar in response to salt stress treatment. Our findings also suggest that the DP rice cultivar acquires a higher level of salt tolerance than the IR28 cultivar, at least a part due to a greater degree of Na+ exclusion and compartmentalization mechanisms provided by HKT1, HAK10, SOS1, and NXH1 transporters.